Investigation on Modal Transient Response Analysis of Engine Crankshaft Structure - M. S. M., Sani; M. M., Noor; M. S. M., Zainury; K., Kadirgama; M. R. M., Rejab; M. M., Rahman (2009)
Crankshaft is a very crucial part in internal combustion engine. This paper presents the finding of mode shape and natural frequency of a 3 cylinder 4 stroke engine crankshafts. Both experimental and computational was carried out to determine the modal parameter or dynamic characteristics which are natural frequency, damping factor and mode shape. The prediction of the dynamic properties of the chassis is great significant to determine the natural frequencies of the structure. Experimental is done by using impact hammer to excite the crankshaft and data recorded using data acquisition system (DAS) connected to sensor located on the crankshaft. Computational modal analysis on crankshaft structure simulated using finite element software. It can be seen from the results that there is a good agreement between the experimental and computational results in terms of modal parameter with small discrepancy. The modal analysis techniques are significant essential for automotive crankshaft structure design.